Deterioration of Cerebral Oxygenation by Aortic Arch Calcification Progression in Patients Undergoing Hemodialysis: A Cross-Sectional Study. (3rd October 2017) - Ito, Kiyonori; Ookawara, Susumu; Okochi, Tomohisa; Ueda, Yuichiro; Kofuji, Masaya; Hayasaka, Hideyuki; Uchida, Takayuki; Miyazawa, Haruhisa; Yanai, Katsunori; Ishii, Hiroki; Kitano, Taisuke; Shindo, Mitsutoshi; et al.
Abstract : Background . Near-infrared spectroscopy revealed that the regional saturation of oxygen (rSO2 ) in cerebral tissue is lower in hemodialysis (HD) patients than in healthy subjects. However, no study has examined the changes in cerebral oxygenation by aortic arch calcification (AAC) progression in HD patients. Methods . A total of 104 HD patients were divided into four groups by AAC grade determined using chest radiography: 23 patients at grade 0, 24 at grade 1, 30 at grade 2, and 27 at grade 3. Differences in clinical parameters, including cerebral rSO2, among AAC grades were investigated and atherosclerotic parameters affecting cerebral rSO2 values were identified. Results . Cerebral rSO2 significantly decreased as AAC progressed (AAC grade 3 versus grade 0, p < 0.01 versus grade 1, p < 0.05 ). Multivariate logistic regression analysis was performed using parameters with p values < 0.20 in univariate analysis between cerebral rSO2 values less than the mean and atherosclerotic parameters. AAC grades 2 and 3, serum phosphate level, and history of smoking were factors associated with the cerebral rSO2 decrease. Conclusions . Cerebral rSO2 significantly decreased as AAC progressed and was independently associated with higher AAC grade, serum phosphate level, and history of smoking.